2018
DOI: 10.1037/xap0000170
|View full text |Cite
|
Sign up to set email alerts
|

Why are background telephone conversations distracting?

Abstract: Telephone conversation is ubiquitous within the office setting. Overhearing a telephone conversation-whereby only one of the two speakers is heard-is subjectively more annoying and objectively more distracting than overhearing a full conversation. The present study sought to determine whether this "halfalogue" effect is attributable to unexpected offsets and onsets within the background speech (acoustic unexpectedness) or to the tendency to predict the unheard part of the conversation (semantic [un]predictabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 94 publications
(287 reference statements)
2
23
0
13
Order By: Relevance
“…This result, however, is consistent with previous studies showing that manipulations designed to increase perceptual demand, such as the perceptual degradation of task-relevant material (Hughes et al, 2013;Marsh, Sörqvist, & Hughes, 2015) or the use of a disfluent i.e. difficultto-read font (Halin et al, 2014;Marsh, Ljung et al, 2018) can reduce or even abolish auditory distraction without having an impact on task performance. According to Sörqvist and Marsh (2015), when task difficulty is high, people make a compensatory upward shift in concentration in order to maintain their desired ttention…”
Section: Resultssupporting
confidence: 91%
“…This result, however, is consistent with previous studies showing that manipulations designed to increase perceptual demand, such as the perceptual degradation of task-relevant material (Hughes et al, 2013;Marsh, Sörqvist, & Hughes, 2015) or the use of a disfluent i.e. difficultto-read font (Halin et al, 2014;Marsh, Ljung et al, 2018) can reduce or even abolish auditory distraction without having an impact on task performance. According to Sörqvist and Marsh (2015), when task difficulty is high, people make a compensatory upward shift in concentration in order to maintain their desired ttention…”
Section: Resultssupporting
confidence: 91%
“…There is some evidence to suggest that the content of the speech may influence the amount of distraction. For example, hearing only one side of a telephone conversation is more distracting than hearing both sides of the conversation, presumably because the former type of speech is less predictable than the latter (Emberson, Lupyan, Goldstein, & Spivey, 2010;Marsh et al, 2018). In a similar fashion, engaging speech may be more likely to attract attention away from the main task and thus lead to a greater disruption in comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…This approach meant that we could for the first time examine any influence of encoding load on auditory distraction without altering the actual visual stimuli across different levels of load (cf. e.g., Halin, Marsh, & Sörqvist, 2015;Hughes et al, 2013;Marsh, Ljung, et al, 2018a;Marsh, Yang, et al, 2018b) which has, in other settings, complicated the interpretation of load effects on selective attention (Benoni & Tsal, 2013;Tsal & Benoni, 2010;Wilson et al, 2011). Experiment 1 showed that high load eliminated the otherwise disruptive effect of a deviant sound within an irrelevant sound sequence (e.g., Hughes et al, 2005) while Experiment 2 showed that the disruptive effect of a changingcompared to steady-state sequence (cf.…”
Section: Discussionmentioning
confidence: 99%
“…On this approach, no limit on processing is necessarily assumed, and the theoretical question shifts to how the potential interference flowing from that processing is cognitively controlled (for an in-depth discussions, see, e.g., Allport, 1993;Neumann, 1996;Tipper, 2001). The present study builds in particular on recent research suggesting that the degree to which task-irrelevant auditory input impinges on task performance is dictated in part by the degree to which top-down control can be imposed to regulate the level of engagement in the focal task (Hughes, Hurlstone, Marsh, Vachon, & Jones, 2013;Marsh, Ljung, et al, 2018a;Marsh, Sörqvist, & Hughes, 2015a;Marsh, Yang, et al, 2018b). When a boost in engagement is promoted by an increase in task demands, or when engagement-control is relatively great in the first place due to a high trait capacity for executive control -as indicated by measures of working memory capacity [WMC]; (Engle & Kane, 2004)-, certain kinds of auditory distraction are attenuated if not eliminated (Hughes et al, 2013;Marsh, Sörqvist, Hodgetts, Beaman, & Jones, 2015a;Marsh, Sörqvist, & Hughes, 2015b;Marsh, Vachon, & Sörqvist, 2017;Sörqvist, 2010; though see Körner, Röer, Buchner, & Bell, 2017;Hughes and Marsh 2019).…”
mentioning
confidence: 99%